Investigating the Relationship between Financial Development and Tourism Management: Evidence from Asian Economies - Hussain, Shehar Yar; Hussain, Muhammad Nasir; Iqbal, Aqsa; Kanwal, Ambereen (iRASD Journal of Economics, 2023)
The purpose of this research is to examine the link between financial development and tourism. The study looks at the relationship between financial development variables including Domestic credit by private sector bank and Broad Money and tourism measures like tourist receipts. The analysis is based on data from an Asian country ranging from 1995 to 2020 and using correlation analysis, co integration first generation (Kao) and Linear regression to investigate the relationship between the variables. Whereas the cross-section dependence and ordinary least square test also used to generate the results. The findings indicate a positive relationship between financial development and tourism, implying that nations with more developed financial systems have greater levels of tourism activity. More study is needed, however, to establish the causal link and understand the underlying processes behind this correlation.